Shear Strength and Behavior of Reinforced Concrete T-Beam with Openings in Both Web and Flange - Kawani, Yousif Yasin Qader; Saeed, Jalal A.; Hasan, Mahdi O. (Sulaimani Journal for Pure and Applied Sciences, 2017)
w campus, The main objective of this research is to study the shear strength and behavior of reinforced concrete T-beam with openings in the web and flanges. The effect of number and location of openings on the shear strength and behavior of the beams is compared with theoretical equations. The experimental program includes casting and testing of thirteen reinforced concrete T-beams, one of which was cast without any openings, while, the others were cast with openings in the web and/or the flanges under mid span point load. The specimens have constant cross section, with 350 mm flange width, 70 mm flange thickness, 150 mm width of the web, 350 mm over all depth of the beam, and 1800 mm clear span. For all the beams the span and steel reinforcements were kept constant. Variables in this study are the location and number of 50mm diameter openings at distance d=300 mm, and 2d=600 mm from the edge of the beams in both the web and/or the flanges. Experimental results showed that, opening in the webs at distance (d) from supports are more effective on the strength decreasing value of the T-beams than others with an opening in the flange at the same distance from the supports. Beams with one opening in webs and/or flanges at distance (d) from supports are more effective on the strength decreasing value of the T-beams than others with two and four openings in the webs and flanges at distance (2d) from the supports. The presence of the web openings at distance (d) from supports reduces the shear capacity about (30.67% to 33.33%) in comparison with control beam, and about (6.67% to 9.33%) for beams with web opening at distance (2d) from the supports. The presence of flange openings at distance (d) from supports reduces the shear capacity about (17.33% to 30.67%) in comparison with control beam, and about (9.33% to 22.67%) for beams with flange opening at distance (2d) from the supports. Beams with opening in both flanges and webs, the presence of openings at distance (d) from supports reduces the shear capacity about (22.67% to 28%) in comparison with control beam, and about (6.67% to 12%) for beams with openings at distance (2d) from the supports.
Keywords: Reinforced concrete Tbeams; Shear strength and behavior; Openings in both flange and web